Risk Factors Of Ovarian Cancer Among The Postmenopausal Women (Journal of Preventive and Social Medicine, 2024)
Background: Ovarian cancer ranks 5thin cancer deaths among women. A woman’s risk of getting ovarian cancer during her lifetime is about 1 in 75. Cancer mainly develops in older women.Methods: The case control study was carried out among 154 respondents in medical oncology department, NIRCH, Dhaka from July 2016 to June 2017. Among the participants, 77 were cases who had ovarian cancer and another 77 were controls who had no ovarian cancer. Convenient sampling technique was used and data were collected by face-to-face interview using a pretested semi-structured questionnaire. Data were entered on to the template of SPSS and analysis was done.Results: The mean age of case and control group were 60.06±7.00 and 59.89±6.96 years respectively. Highest number of respondents were illiterate. Majority came from rural area and had no personal monthly income. Most of them were taken high fiber diet, 83.1% in case and 77.9% in control group. About 80.5% in case and 66.2% in control group had BMI ≥25 kg/m2. Sedentary workers 40.3% in case and 13.0% in control group; moderate workers were 31.2% in case and 20.8% in control group and hard workers were 28.5% and 66.2% in case and control group respectively. The mean age of menarche 12.02±1.19 years and 12.87±1.30 years in case and control group respectively and mean age of menopause in case and in control groups respectively 51.54±2.39 and 49.61±1.29 years. In case group 49.3% had early term pregnancy whereas in control group 9.5% had early term pregnancy; in case group 82.1% and in control group 86.5% had breast feeding history. Around 16.9% in case group and 27.3% in control group used to take OCP. Significantly more respondents 6.5% in case group had personal H/O breast cancer than control group. Positive family history of breast and ovarian cancer was found 16.9% in case group and 2.6% in control group. In binary logistic regression analysis for risk factors of OC was found that sedentary activity was associated with increased risk, increased BMI (≥25 kg/m2), early age of menarche (≤12 years), late age of menopause (>51 years), nullipara and early term pregnancy. Family H/O breast or ovarian cancer significantly associated with development of ovarian cancer.Conclusion: Ovarian cancer observed more in older age group (≥60 years) among sedentary worker with high body mass index (≥25 kg/m2). Early age of menarche (≤12 years), late menopause (>50 years), never having given birth to a child in life time, early term of pregnancy and family history of breast and ovarian cancer were significantly associated with ovarian cancer among post-menopausal women.JOPSOM 2021; 41(2):28-35